Integration of absorption refrigeration systems into rankine power cycles to reduce water consumption: An economic analysis. (15th August 2020) - Ramírez, F. Javier; Salgado, R.; Almendros-Ibáñez, J.A.; Belmonte, J.F.; Molina, A.E.
Abstract: This work presents the economic modeling and analysis of a thermoelectric steam power plant (SPP) cooled with an air-cooled heat exchanger (ACHX) and using an absorption refrigeration system (ARS) as an intermediary, as discussed in Salgado et al., 2017. This novel configuration has the advantage of not consuming fresh water in the cooling system, which is of special interest in locations where water is scarce or expensive. Based on the thermodynamic analysis of this SPP configuration (considering three different power ranges: 5 MW, 50 MW, and 200 MW, and different ambient temperatures from 5°C to 40°C), economic and sensitivity analyses were conducted to determine the cost-effectiveness and profitability of the power plant. Finally, a comparative analysis was conducted to test the economic outcomes of the SPPs using the proposed ARS compared with conventional refrigeration devices based on water cooling and dry cooling technologies. The results show that conventional evaporative cooling towers are the best solution from an economic perspective. Nevertheless, in regions where water is not easily accessible, the proposed ARS achieves better economic outcomes than the conventional ACHX when the ambient temperature is beyond the range of 17.5°C–22.5°C, depending on the power rating of the plant. Highlights: Economic and profitability assessment of ARS as heat rejection in power cycles. ARS solution as appropriate alternative for warm and water-scarce locations. Comparative analysis with conventional refrigeration devices. Sensitivity analysis of the key parameters affecting the economic performance. Parametric analysis for optimal electricity spot price and water-fuel costs.